Study of naturally occurring radionuclides and stable metals in soils of West Malaysia / Ghazwa Hatem Takleef Alzubaidi - Ghazwa Hatem, Takleef Alzubaidi (2022)
Linking scientific information to environmental parameters that influence radionuclide dispersion in response to chemical, physical, and biological responses within the soil profile is still lacking, particularly in the tropics. Bearing in mind the likelihood that nuclear energy will be a substantial component of social and economic development across the tropics in future decades due to climate change, this study sought to evaluate the behavior of radionuclides in the tropical environment. The primary objective of this study was to investigate the vertical distribution of the activities of natural radionuclides 226Ra, 232Th, and 40K, and chemical elements in different areas of tropical soils in order to obtain a common understanding of the reactive environment factors associated with the reactions of radionuclides, as well as, assessing radiation risks according to this activity. A total of 228 soil samples were collected randomly at depths of 0-10, 10-20, 20-30 and 30-40 cm, from August 2013 to October 2017 from six agricultural regions of Peninsular Malaysia. In addition, 40 soil samples were collected at one depth of 0-40 cm from a paddy field in Kedah, Malaysia, to study seasonal changes that may have a potential impact on radionuclides behavior, 20 samples were collected during the wet season or growing season (March-April) and 20 samples during the dry season or harvest season (June-August). In all the examined study areas, the mean concentration values of 226Ra, 232Th, and 40K were comparable higher than the global averages provided by the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR). The study areas did not show clear spatial divergence in the calculated values of radionuclide and chemical element concentrations. The study of the distribution patterns of radionuclides and elements were affected by the same mechanisms and factors within the soil profile and adopted a consistent behavior within the interactive environment of tropical soils. The calculated mean values of the radium equivalent activity (Raeq) for the study areas did not exceed the acceptable safe limit of 370 Bq.kg-1 recommended by UNSCEAR. The calculated values of the mean absorbed dose rate (D) for the study areas were higher than the overall global value of 60 n Gy h- 1, where the mean values ranged from 103.26 to 113.30 n Gy h−1. The measured mean values of the annual effective dose equivalent (AEDE) for the study areas fall within the recommended levels by the International Committee on Radiological Protection (ICRP) which is 1 mSv year−1. The measured values of the external hazard index (Hex) for the study areas did not exceed the acceptable safe limit value (less than or equal to one). Radionuclides showed a similar tendency in most of the study areas in their correlations with chemical soil components. These consistent correlations indicate that radionuclide mobility underwent the same migration mechanisms and that its behavior was modified by many unique features of the tropical environment.